2020
DOI: 10.33387/j.edu.v18i2.2119
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kemampuan Penalaran Statistis Mahasiswa Melalui Pembelajaran Berbasis Proyek Berbantuan Ict

Abstract: The problem with this research is the students’ low ability of statistical reasoning. This study aims to determine the students’ achievement and improvement of statical reasoning through project-based learning with ICT assistance. This research was in the form of a quasi-experimental design of the pretest-posttest control group. The numbers of samples of this study were 51 students taken by purposive sampling from 102 students who took statistics introductory lectures. This study has two variables, namely: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
1
0
4
Order By: Relevance
“…Hasil tersebut memperlihatkan bahwa mahasiswa sudah terbiasa menggunakan media yang berakitan dengan ICT, khususnya PPT. Hal tersebut mendukung hasil-hasil penelitian sebelumnya yang menyebutkan bahwa mahasiswa (peserta didik) terbiasa menggunakan ICT dalam proses pembelajaran (La Nani, Bakar, & Saidi, 2020;Nurdiayana & Suanto, 2020;Nazar et al, 2020), khususnya PPT (Juraida, 2016;Suardi., 2020;Uningal & Widiatningrum, 2020).…”
Section: Pembahasanunclassified
“…Hasil tersebut memperlihatkan bahwa mahasiswa sudah terbiasa menggunakan media yang berakitan dengan ICT, khususnya PPT. Hal tersebut mendukung hasil-hasil penelitian sebelumnya yang menyebutkan bahwa mahasiswa (peserta didik) terbiasa menggunakan ICT dalam proses pembelajaran (La Nani, Bakar, & Saidi, 2020;Nurdiayana & Suanto, 2020;Nazar et al, 2020), khususnya PPT (Juraida, 2016;Suardi., 2020;Uningal & Widiatningrum, 2020).…”
Section: Pembahasanunclassified
“…Mengembangkan kemampuan penalaran statistis diperlukan proses interaksi antar mahasiswa dengan sumber belajar, seperti: teman sebaya, dosen atau ahli (La Nani, 2015b). Terciptanyan interaksi mahasiswa tersebut melalui suatu komunikasi aktif secara formal dalam kegiatan pembelajaran.…”
Section: Pendahuluanunclassified
“…Penerapan PBP dalam mempelajari pengantar statistika dapat diintegrasikan dengan penggunaan software SPSS. Software SPSS sebagai suatu fasilitas ICT yang bergantung pada computer, berfungsi membantu menganalisis data statistik (La Nani, 2015b, 2016. Fletcher dalam Kusumah (2011), mengemukakan bahwa potensi teknologi komputer sebagai media dalam pembelajaran matematika sangat besar.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Research Results from Nielsen et al (2010), Struyven et al (2010), andLa Nani et al (2020), revealed that a learning model that can improve students' learning abilities and achievement is a project-based learning model (PBL). Through PBL, students are prepared cognitively and emotionally to solve complex challenges collaboratively.…”
Section: Introductionmentioning
confidence: 99%